Kinerja Usahatani Kopi Liberika di Kecamatan Betara Kabupaten Tanjung Jabung Barat - Amalia, Dwi Nurul; Kurniati, Yuyun; Wahyuni, Ira (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2022)
The research aims to 1) to know the description of liberica coffee farming in Betara District, 2) to analyze the income of liberica coffee farming in Betara District, and 3) to analyze the feasibility level of liberica coffee farming in Betara District. The research was conducted in Betara District, Tanjung Jabung Barat Regency. The data used were primary and secondary data. The sampling technique was simple random sampling. The number of sample farmers was 77 people, with a division of 44 people in Mekar Jawa Village and 33 people in Bunga Tanjung Village. Data analysis used descriptive and quantitative analysis of income and feasibility of liberica coffee farming with R/C ratio and π/C ratio. The results showed 1) the land area owned by liberica coffee farmers in the study area averaged 1,95 Ha. The planting pattern of liberica coffee is made in a mixed farming technique with areca nut. Labor activities in liberica coffee farming include maintenance, harvest, and post-harvest. 2) Average production of 239 Kg/Ha/Year, with total costs of Rp 1.925.874/Ha/Year, the revenue of Rp. 7,170,000/ha/year and income earned of Rp. 5,244,153/ha/year. Liberica coffee income in the study area is still relatively low. This means that Liberika coffee cannot be used as the primary source of income for farmers and can only be an additional source of income. 3) The results of the R / C analysis of the liberica coffee farming ratio of 3.72 and π / C ratio analysis of 272.3% means that it is feasible to cultivate.